Metallographic and neutron diffraction analysis on microstructural evolution and control in ancient Indian high carbon steel. (1st November 2021) - Park, Jang‐Sik; Grazzi, Francesco; Scherillo, Antonella; Shinde, Vasant
Abstract: Despite the credit attributed to India for the early production of high carbon steel, not much is known about Indian contribution to the implementation of a pertinent fabrication technique without which this special material might have little practical value. A metallographic examination of a small iron lump and an iron sheet, both excavated from the second BC to second AD century site at Junnar in India, provided evidence that the production of high carbon steel was stimulated by a sophisticated technique practiced for the control of carbide precipitation in such a peculiar material. In addition, neutron diffraction analysis on one of the objects, the iron sheet, produced key information defining the thermo‐mechanical treatments applied. An anisotropy in the orientation of cementite grains, similar to one of those documented for the so‐called Damascus swords, was also confirmed. A detailed account of the analytical results is presented, suggesting that a proper technique for the control of microstructural evolution in high carbon steel was fully established in India much earlier than the beginning of the Damascus steel tradition, which must have been inspired by technologies long practiced in India.